Effect of moderate beer consumption (with and without ethanol) on osteoporosis in early postmenopausal women: Results of a pilot parallel clinical trial - Trius-Soler, Marta; Tresserra-Rimbau, Anna; Moreno, Juan J.; Peris, Pilar; Estruch, Ramon; Lamuela-Raventós, Rosa M. (Frontiers in Nutrition, 2022)
Osteoporosis is a chronic progressive bone disease characterized by low bone mineral density (BMD) and micro-architectural deterioration of bone tissue, leading to an increase in bone fragility and the risk of fractures. A well-known risk factor for bone loss is postmenopausal status. Beer may have a protective effect against osteoporosis associated with its content of silicon, polyphenols, iso-α-acids and ethanol, and its moderate consumption may therefore help to reduce bone loss in postmenopausal women. Accordingly, a 2-year controlled clinical intervention study was conducted to evaluate if a moderate daily intake of beer with (AB) or without alcohol (NAB) could have beneficial effects on bone tissue. A total of 31 postmenopausal women were assigned to 3 study groups: 15 were administered AB (330 mL/day) and 6, NAB (660 mL/day), whereas the 10 in the control group refrained from consuming alcohol, NAB, and hop-related products. At baseline and subsequent assessment visits, samples of plasma and urine were taken to analyze biochemical parameters, and data on medical history, diet, and exercise were collected. BMD and the trabecular bone score (TBS) were determined by dual-energy X-ray absorptiometry. Markers of bone formation (bone alkaline phosphatase [BAP] and N-propeptide of type I collagen [PINP]) and bone resorption (N-telopeptide of type I collagen [NTX] and C-telopeptide of type I collagen [CTX]) were determined annually. Bone formation markers had increased in the AB and NAB groups compared to the control after the two-year intervention. However, the evolution of BMD and TBS did not differ among the three groups throughout the study period. Therefore, according to the findings of this pilot study, moderate beer intake does not seem to have a protective effect against bone loss in early post-menopausal women.